Ladd's Band - A Case Report - Covizzi, Ian Vilas Boas; de Souza, Tricia Aline Ribeiro Pattini; Scalon, Thatiana; Boas, João Renato Villas; Gil, Guilherme Trojillo; Neto, Wilson Mantovani Robelo; Cheirubim, Marcelo; Covizzi, Uderlei Doniseti Silveira (Seven Editora, 2023)
Ladd bands consist of a congenital pathology of peritoneal embryogenesis characterized by the formation of a fibrotic area between bowel loops that, combined with a malrotation of the bowel, can cause intestinal obstruction or in other cases, facilitate the development of the volvulus. Because it is congenital, it has a predominance in childhood and its diagnosis must be early, so that surgical correction can be performed on an urgent basis, given the high risk of vascular involvement and intestinal necrosis. In this work we present the case of a 13 year old male, with an acute presentation of intestinal malrotation, but with a history of chronic symptoms of this pathology, who were submitted to laparotomy and performed ileodistal dissection with significant improvement of the case. Knowing how to diagnose this congenital anomaly early is the main step towards a better quality of life for the patient. DOI: https://doi.org/10.56238/colleinternhealthscienv1-099